Rancang Bangun Deteksi Bentuk Wajah Untuk Menentukan Gaya Rambut Menggunakan Algoritma CNN - Mahardika Yoshi Putra (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
In appearance, hair is an important aspect. In this modern era, hairstyles are becoming more and more varied. So, a lot of teenage men have trouble determining a suitable hairstyle. One factor in determining hairstyles is the shape of their faces. Often, teenagers don't match the haircut they've chosen. It can make you feel less confident and feel less in terms of appearance. Because it requires a system to recognize the shape of the face and determine the appropriate hairstyle. The most common method of grouping is the CNN method. In this study, the recommended hairstyles of male hair models and facial shapes detected are Oval, Box, Long Square, and Round. This study has accuracy with an average presentation of 85%.